Just what is critical race theory, and what is it doing in British sociology? From "BritCrit" to the racialized social system approach. (24th December 2020) - Meghji, Ali
Abstract: Critical race theory is growing in popularity in Britain. However, critics and advocates of critical race theory (CRT) in Britain have neglected the racialized social system approach. Through ignoring this approach, critics have thus "missed the target" in their rebuttals of CRT, while advocates of CRT have downplayed the strength of critical race analysis. By contrast, in this paper, I argue that that through the racialized social system approach, critical race theory has the conceptual flexibility to study British society. As a practical social theory, critical race theory provides us with the tools to study the realities and reproduction of racial inequality. To demonstrate this strength of CRT, and to demonstrate its theoretical nature, I discuss the conceptual framework of the racialized social system approach, paying specific attention to the notions of social space, the racial structure and racial interests; the racialized interaction order, racialized emotions, and structure and agency; and racial ideology, racial grammar, and racialized cognition.